The Islamic Values Representations of Female Main Character in Novels by Habiburrahman El-Shirazy - Alifiya Habiba, Sri Penny; Nuryatin, Agus (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
Habiburrahman El-Shirazy’s novel presence reveals aesthetic values and is expected to realize its universal values in social life, as for example the values of religion, education, moral, ethic, social, and etc. His works contain religious valued endeavors, to present Islamic teaching instilled into each character, both male and female. The problems are how the attitude of the main female character is, how Islamic values of the novels is, and how to represent Islamic teachings of the novel. The research method used covers extrinsic approach by combining the literature and its thought (Wellek and Austin Warren), data and other data sources, its data collection, validity, and technique of data analyzing. The findings are the attitude of the main character is pious, obedient to her husband, parents, eager to study, responsible, generous, and handy. The values are found are aqidah, the worship values, its values and Islamic teaching representations are; Aqidah (ilahiyat, prophecy, ruhaniyat, samiyat), syariat (mahdah worships dan ghairu mahdah worships), Akhlak (the righteous attitude).